Psychological distress and burnout among counsellors working in health information helplines - Suri, Kanika; Hegde, Shailendra Kumar B.; Sadanand, Shilpa; Randhawa, Sonali; Bambrah, Hardeep Singh; Turlapati, Swarnalatha (International Journal Of Community Medicine And Public Health, 2020)
Background: PSMRI has large numbers of health workforce working in health information helpline (HIHL) in India. Aiming to understand stress, burnout among counsellors working in HIHLs, India. The study aimed to understand the level of stress and linkages and how the health workforce can go through distress working in helplines. Methods: Individual study interviews were conducted across six states. Socio-demographic details, medical history and lifestyle information, collected. General health questionnaire (GHQ-28) and Copenhagen burnout inventory (CBI)-tools. Results: 16.9%- work-related burnout, 15.5%- client-related burnout and more than 1/4th (25.3%) had personal burnout. Level of psychological distress and burnout among counsellors working in helplines was high. Conclusions: The study shows on how the counsellors working in the helplines go through psychological distress and burnout. It also leads to mechanisms that leads to the awareness of psychological distress faced by mental health professionals, and training for support was initiated to develop a mental health platform.